Click, Connect, Recruit: A Systematic Review of the Role of Social Media in Employee Recruitment - Siddik, Agung Sukma Adiguna; Soewignyo, Tonny; Mandagi, Deske W. (SAFE-Network, 2024)
The development of technology is a revolution that is good for human life, especially having a good impact on the business sector as well. The existence of technology which is currently highly developed and modified in such a way, makes the tasks carried out more flexible, effective and efficient. The use of social media in recruitment methods provides navigation to stakeholders with the resulting flexibility being considered effective and efficient. This systematic review was made in line with previous research which previously discussed the effectiveness of social media in the recruitment process. The pandemic that hit provided adjustments for the Human Resources department in the process of recruiting new employees. It is stated that the use of technology and social media is effective in obtaining new sources of labor who have character, skills and match the company's qualifications. The results revealed that social media plays a crucial role in HRM beyond recruitment, impacting employer branding, employee engagement, and talent retention. E-recruitment has revolutionized hiring by accessing diverse talent pools and catering to Generation Z preferences. Despite challenges, social media enables personalized candidate interactions and targeted outreach. Integrating AI and analytics offers more efficient and data-driven talent acquisition and management strategies.